The dynamism of the new economy: Non-standard employment and access to social security in EU-28 - Sonja Avlijaš (London School of Economics and Political Science (LSE), European Institute, 2019)
This paper examines the prevalence of non-standard workers in EU-28, rules for accessing social security, and these workers' risk of not being able to access it. It focuses on temporary and part-time workers, and the self-employed, and offers a particularly detailed analysis of their access to unemployment benefits. It focuses on eligibility, adequacy (net income replacement rates) and identifies those workers which are at the greatest risk of either not receiving benefits or receiving low benefits. It offers a special overview of foreign non-standard workers, who may be particularly vulnerable due to the absence of citizenship in the host country. The paper also analyses access to maternity and sickness benefits for these three groups of workers, as well as their access to pensions. Its key contribution is in bringing together the different dimensions of disadvantage that non-standard workers face vis-à-vis access to social protection. This allows us to comprehensively assess the adaptation of national social security systems across EU-28 to the changing world of work over the past 10 years. The paper shows that there is a lot of variation between the Member States, both in the structure of their social security systems, as well as the prevalence of non-standard work. Most notably, the paper concludes that: i) access to unemployment benefits is the most challenging component of welfare state provision for people in non-standard employment; ii) policy reforms vis-à-vis access to social benefits have improved the status of non-standard workers in several countries, while they have worsened it in others, particularly in Bulgaria, Ireland and Latvia; iii) some Eastern European countries can offer lessons to other Member States due to their experiences with labour market challenges during transition and the subsequent adaptations of their social security systems to greater labour market flexibility. The paper also implies that a country's policy towards nonstandard work cannot be examined in isolation from its labour market conditions, as well as its growth model, and that uniform policy solutions for non-standard work cannot be applied across EU-28.
Keywords: 330; non-standard workers; new economy; social security; unemployment benefit; maternity benefit; sickness benefit; income replacement convergence